Broad Spectrum Deubiquitinase Inhibition Induces Both Apoptosis and Ferroptosis in Cancer Cells - Yang, Li; Chen, Xin; Yang, Qianqian; Chen, Jinghong; Huang, Qingtian; Yao, Leyi; Yan, Ding; Wu, Jiawen; Zhang, Peiquan; Tang, Daolin; Zhong, Nanshan; Liu, Jinbao (Frontiers in Oncology, 2020)
Proteasomal deubiquitinase (DUB) inhibition has been found to be effective in experimental cancer therapy by inducing proteasome inhibition and apoptosis. Ferroptosis is a form of regulated cell death characterized by an iron-dependent lipid peroxidation. Antioxidant enzyme glutathione peroxidase 4 (GPX4) plays a key role in blocking ferroptosis through directly reducing phospholipid hydroperoxides production. Since cytoplasmic DUB inhibition can promote protein degradation in the cell, we hypothesize that DUB inhibition induces GPX4 degradation. Here we used palladium pyrithione complex (PdPT), a broad spectrum deubiquitinase inhibitor, to explore its cell death induction and anti-cancer effect in vitro, ex vivo and in vivo. Mechanically, caspase activation and GPX4 protein degradation are required for PdPT-induced apoptosis and ferroptosis, respectively. Notably, PdPT-induced multiple deubiquitinase inhibition is essential for proteasomal degradation of GPX4. These findings not only identify a novel mechanism of posttranslational modification of GPX4 in ferroptosis, but also suggest a potential anti-caner therapeutic strategy using Pan-DUB inhibition.